Quality check for customer benefit in bus transport system through statistical control charts and gauge R & R - Rafique, M.Z. (Research India Publications, 2016)
Travelling is one of the basic necessities of every human being. It is a natural behavior of every traveler to desire âarrival as plannedâ when using any transportation system. In order to fulfill this desire, travelling through Bus is one of the most selected options. The passengerâs decision regarding selection of bus services entirely depends upon service quality. It has been observed that, if the bus service quality is poor, specifically in terms of timing, then it results in fair chances of loss of ridership because of annoyance due to delays which results in anxiety. The focus of this research work is to measure quality of bus transport system by considering one of famous bus service as a case study. The aim is to utilize tool named as âControl chartsâ and âGauge R & Râ to check its quality and services. A detailed X-bar and R-bar charts are produced based on frequency of timing of buses from one station to another and on the same sample the gauge R & R results in 24 which clearly indicates that the selected bus service is running in control situation due to utilization of modern technologies and recommends use of modern technologies to other bus services. However factors like uncertainty of road traffic and sudden accidents on road obviates to achieve gauge R & R value within 10. Â© Research India Publications.